Teachers' readiness to adopt online teaching amid COVID-19 lockdown and perceived stress: pain or panacea?. Issue 6 (17th May 2021) - Mehta, Prashant
Abstract : Purpose: Prolonged closure of educational institutions prompted authorities to adopt online teaching as an alternative method to impart education. The purpose of this study is to investigate the readiness on the part of teachers to switch/adopt online teaching as a part of their pedagogy. Also, this study analyses relationship between perceived stress (PS) and readiness to change (RTC)/adopt. Design/methodology/approach: All the constructs were adapted from established scales, exploratory factor analysis confirmed item loadings on the appropriate constructs. Convenience sampling was used for data collection; owing to COVID-19 this appeared to be the only viable method. Partial least square structural equation modelling was used for analysis of data. Findings: Results from this study indicate that 32.2% variance in RTC is accounted for by exogenous constructs perceived usefulness, perceived ease of use and autonomy (AUT). Although f2 effect size pointed towards non-significance of AUT in predicting RTC (path coefficients were found to be significant for all the exogenous constructs). Also, RTC accounted for 32.6% variance in PS. To assess the predictive relevance of the model, blindfolding procedure was used to obtain Q2 values (Q2PS = 0.231; Q2RTC = 0.243). Positive Q2 values provide support for the model's predictive relevance. Research limitations/implications: Data were collected from teachers employed in urban public schools. A complete picture can be obtained by involving teachers from rural public and state-run schools. Practical implications: Teachers' readiness to adopt online teaching as a part of their pedagogy may act as a starting point for the policymakers to design properly structured training programs for teachers that minimise stress levels. Social implications: If not handled properly, the society may end with either loss of learning to one generation or a major chunk of stressed-out teaching populations or both. Originality/value: To the best of the author's knowledge, this study is probably the first one focusing on sudden shift to online teaching and PS.